Reintroducing Global Harmony in Islamic Religious Education Based on Local Wisdom (Samin Community) Bojonegoro - Mashani, Nur; Setiawan, Budi (Proceedings of Annual Conference for Muslim Scholars, 2025)
This article presents the results of research on reintroducing global harmony in Islamic education based on local wisdom among the Samin community in Bojonegoro. The purpose of this study is to describe the noble values in the local wisdom of the Samin community in Bojonegoro regarding harmonious and peaceful activities in a multicultural society. This research is qualitative in nature, involving observation of the traditional life of the Samin community and in-depth interviews with local community leaders. The results of the study show several local wisdoms in the Samin community of Bojonegoro, namely: ngelmu iku sejatine dhewe, ngudi ilmu, ponco soco, ngluruk tanpa rupo, nyawiji sepi ing pamrih, nyawiji ngluruk, ngganem sepi ing ngluruk, and ngalembono. This study contributes to a deeper understanding of the balance between global harmony in Islamic religious education and local culture, providing new insights for researchers, practitioners, and readers interested in this field